THE MAIN TASKS OF TOXICOLOGICAL CHEMISTRY - Sh. Sh. Obloqulov (Galaxy International Interdisciplinary Research Journal, 2022)
Humanity coexists in the modern world with natural disasters, man-made catastrophes, labor activities, and other incidental incidents that happen in daily home life. Additionally, criminal and suicide instances with an unidentified chemical cause do occur. In these circumstances, it is important to explain and assess the events that occurred utilizing, among other sciences, the achievements of toxicological chemistry. This article will discuss the emergence, significant developments in toxicological chemistry, the physiological changes brought on by exposure to hazardous substances, the underlying causes, and the various categories of toxic substances.